Building Religious Harmony with A Humanistic Education: The Potential and Strategies to Overcome the Conflict Threat in Pesantren - Musthofa Musthofa; Nasikhin Nasikhin; Mohammad Rofiq; Qasem Muhammadi (STAI Hubbulwathan Duri, 2025)
Religious harmony is increasingly challenged by rising fanaticism, exclusivity, and intolerance, particularly in religious educational settings. This study analyzes the strategy of fostering religious harmony through a humanistic education approach at Pesantren Khaffiah Village in Batang Regency, Central Java. Employing a qualitative case study design, the research explores the pesantren’s educational practices and their role in promoting interreligious understanding. Data were collected through observations, interviews, and documentation to examine how humanistic values are integrated into religious instruction. The study identifies four main threats to religious harmony: excessive fanaticism, social exclusivity, the spread of intolerant ideologies, and internal conflict. These issues are rooted in a limited understanding of peaceful religious teachings among new students, social isolation, and socio-economic disparities. In response, Pesantren Khaffiah implements a four-pronged strategy grounded in Islamic humanism. This includes (1) teaching classical Islamic texts emphasizing peace and ethics, such as Ihya’ Ulumuddin and Riyadhus Shalihin, (2) organizing a “Humanistic Learning Day” that addresses humanitarian issues, (3) launching the “Santri Peduli” social service program to foster inter-organizational cooperation, and (4) offering the “Art of Harmony” extracurricular initiative to build tolerance through artistic collaboration. These findings contribute to the development of a humanistic education model aimed at promoting religious harmony in Islamic boarding schools. The model offers practical insights for Islamic educational institutions seeking to nurture peaceful coexistence in diverse religious contexts.